Kinesthetic Learning Style Preferences: A Survey of Indonesian EFL Learners by Gender: Preferensi Gaya Belajar Kinestetik: Survei Pembelajar EFL Indonesia Berdasarkan Gender - Tyas, Peptia Asrining; Safitri, Mega (JEES (Journal of English Educators Society), 2017)
This study investigated predominant learning style of 3rd semester students of English Language Education Program in Faculty of Cultural Studies at Universitas Brawijaya according to gender. Purposive sampling was used for this research and the sampling in this research was 100 students consist of 34 male students and 66 female students taken from 3rd semester English Department students of Faculty of Cultural Studies at Universitas Brawijaya. All participants were administered an Indonesian translated version of Reid’s (1984) Perceptual Learning Style Preference Questionnaire consisting of Visual, Auditory, Kinesthetic, Tactile, Group, and Individual, included 30 items. This study used quantitative survey design and Microsoft Excel 2007 as the analysis software. The validity and the reliability of this research were calculated by SPSS v.21. The result indicated that predominant male’s learning style was Kinesthetic and estimated by 14 male students (41%) while female students become Kinesthetic and Group and estimated the same percentage, 21 students (332%) for Kinesthetic and 21 (32%) students for Group. The result of the study also shows that both male and female tend to be Kinesthetic. It is suggested that to the English department to adjust the academic activities with the learning styles to enhance educational achievement and encouraging students take responsibility in their whole learning.